Probiotics and Vitamin D for Gastrointestinal Damage in Burn Injury - Gracia Widia Putri; I Gusti Putu Hendra Sanjaya; I Gusti Ayu Sri Mahendra Dewi; Agus Roy Rusly Hariantana Hamid; Putu Anda Tusta Adiputra (Eduvest - Journal of Universal Studies, 2025)
Curling’s ulcer, a stress-induced gastrointestinal injury, commonly occurs in patients with major burns due to ischemia and mucosal necrosis. Complications may include perforation, hemorrhagic shock, and death. While standard treatments involve PPIs, sucralfate, and early enteral feeding, probiotics may help restore gut microbiota, and vitamin D can reduce inflammation and dysbiosis. However, studies on their combined efficacy remain limited, particularly in Indonesia. This research aims to evaluate whether oral probiotics and vitamin D reduce TNF-α levels and gastrointestinal damage in Wistar rats with major burns. The study employed an experimental design using 32 Wistar rats with 25% TBSA burns. Subjects were divided into four groups: control (K), probiotics only (P1), vitamin D only (P2), and probiotics + vitamin D (P3). Interventions were administered for two weeks. Measured parameters included blood and tissue TNF-α levels, as well as gastric and intestinal histopathology. Data were analyzed using SPSS. Results showed that group P3 had the lowest tissue TNF-α levels (136.11 ± 50.14; p = 0.046) and intestinal mucosal thickness (914.54 ± 170.08; p = 0.007). Indicators of gastric damage—macrophage count, necrosis, and bleeding—were significantly reduced in the treatment groups (p = 0.000). No significant difference was observed in villi width (p = 0.974). Combined oral probiotics and vitamin D significantly reduced tissue TNF-α levels and gastrointestinal damage, with better outcomes than single-agent treatments. This combination therapy shows potential as an adjunctive approach for gastrointestinal protection in major burns.